Decreased rates of terpene emissions in Ornithopus compressus L. and Trifolium striatum L. by ozone exposure and nitrogen fertilization. - Llusia, Joan; Bermejo-Bermejo, Victoria; Calvete-Sogo, Héctor; Penuelas, Josep (Environmental pollution (Barking, Essex : 1987), 2014)
Increasing tropospheric ozone (O3) and nitrogen soil availability (N) are two of the main drivers of global change. They both may affect gas exchange, including plant emission of volatiles such as terpenes. We conducted an experiment using open-top chambers to analyze these possible effects on two leguminous species of Mediterranean pastures that are known to have different O3 sensitivity, Ornithopus compressus and Trifolium striatum. O3 exposure and N fertilization did not affect the photosynthetic rates of O. compressus and T. striatum, although O3 tended to induce an increase in the stomatal conductance of both species, especially T. striatum, the most sensitive species. O3 and N soil availability reduced the emission of terpenes in O. compressus and T. striatum. If these responses are confirmed as a general pattern, O3 could affect the competitiveness of these species.
Keywords: Annual pastures; BVOCS; Emissions; Gas exchange; legumes; Nitrogen deposition; Ozone; terpenes

Foliar CO2 in a holm oak forest subjected to 15 years of climate change simulation - Ogaya, Romà; Llusia, Joan; Barbeta, Adrià; Asensio, Dolores; Liu, Daijun; Alessio, Giorgio Arturo; Penuelas, Josep (Plant Science, 2014)
A long-term experimental drought to simulate future expected climatic conditions for Mediterranean forests, a 15% decrease in soil moisture for the following decades, was conducted in a holm oak forest since 1999. Net photosynthetic rate, stomatal conductance and leaf water potential were measured from 1999 to 2013 in Quercus ilex and Phillyrea latifolia, two co-dominant species of this forest. These measurements were performed in four plots, two of them received the drought treatment and the two other plots were control plots. The three studied variables decreased with increases in VPD and decreases in soil moisture in both species, but the decrease of leaf water potential during summer drought was larger in P. latifolia, whereas Q. ilex reached higher net photosynthetic rates and stomatal conductance values during rainy periods than P. latifolia. The drought treatment decreased ca. 8% the net photosynthetic rates during the overall studied period in both Q. ilex and P. latifolia, whereas there were just non-significant trends toward a decrease in leaf water potential and stomatal conductance induced by drought treatment. Future drier climate may lead to a decrease in the carbon balance of Mediterranean species, and some shrub species well resistant to drought could gain competitive advantage relative to Q. ilex, currently the dominant species of this forest.
Keywords: climate change; Drought; mediterranean forest; phillyrea latifolia; photosynthetic rates; Quercus ilex

Seasonal variations in terpene emission factors of dominant species in four ecosystems in NE Spain - Llusia, Joan; Penuelas, Josep; Guenther, Alex; Rapparini, Francesca (Atmospheric Environment, 2013)
We studied the daily patterns in the rates of foliar terpene emissions by four typical species from the Mediterranean region in two days of early spring and two days of summer in 4 localities of increasing biomass cover in Northern Spain. The species studied were Thymelaea tinctoria (in Monegros), Quercus coccifera (in Garraf), Quercus ilex (in Prades) and Fagus sylvatica (in Montseny). Of the total 43 VOCs detected, 23 were monoterpenes, 5 sesquiterpenes and 15 were not terpenes. Sesquiterpenes were the main terpenes emitted from T. tinctoria. Total VOC emission rates were on average about 15 times higher in summer than in early spring. The maximum rates of emission were recorded around midday. Emissions nearly stopped in the dark. No significant differences were found for nocturnal total terpene emission rates between places and seasons. The seasonal variations in the rate of terpene emissions and in their chemical composition can be explained mainly by dramatic changes in emission factors (emission capacity) associated in some cases, such as for beech trees, with very different foliar ontogenical characteristics between spring and summer. The results show that temperature and light-standardised emission rates were on average about 15 times higher in summer than in early spring, which, corroborating other works, calls to attention when applying the same emission factor in modelling throughout the different seasons of the year.
Keywords: climatic gradient; Emission rates; Mediterranean ecosystems; Seasonality; terpenes

Seasonal variations in terpene emission factors of dominant species in four ecosystems in NE Spain - Llusia, Joan; Penuelas, Josep; Guenther, Alex; Rapparini, Francesca (Atmospheric Environment, 2013)
We studied the daily patterns in the rates of foliar terpene emissions by four typical species from the Mediterranean region in two days of early spring and two days of summer in 4 localities of increasing biomass cover in Northern Spain. The species studied were Thymelaea tinctoria (in Monegros), Quercus coccifera (in Garraf), Quercus ilex (in Prades) and Fagus sylvatica (in Montseny). Of the total 43 VOCs detected, 23 were monoterpenes, 5 sesquiterpenes and 15 were not terpenes. Sesquiterpenes were the main terpenes emitted from T. tinctoria. Total VOC emission rates were on average about 15 times higher in summer than in early spring. The maximum rates of emission were recorded around midday. Emissions nearly stopped in the dark. No significant differences were found for nocturnal total terpene emission rates between places and seasons. The seasonal variations in the rate of terpene emissions and in their chemical composition can be explained mainly by dramatic changes in emission factors (emission capacity) associated in some cases, such as for beech trees, with very different foliar ontogenical characteristics between spring and summer. The results show that temperature and light-standardised emission rates were on average about 15 times higher in summer than in early spring, which, corroborating other works, calls to attention when applying the same emission factor in modelling throughout the different seasons of the year.
Keywords: climatic gradient; Emission rates; Mediterranean ecosystems; Seasonality; terpenes

Seasonal changes in the daily emission rates of terpenes by Quercus ilex and the atmospheric concentrations of terpenes in the natural park of Montseny, NE Spain - Llusia, Joan; Penuelas, Josep; Seco, Roger; Filella, Iolanda (Journal of Atmospheric Chemistry, 2012)
We studied the daily patterns in the rates of terpene emissions by the montane holm oak, Quercus ilex, in three typical days of winter and three typical days of summer in Montseny, a natural park near Barcelona, and related them to the air concentrations of terpenes, ozone and NO2 . Terpene emission rates were about 10 times higher in summer than in winter. Emissions virtually stopped in the dark. In both seasons, rates of terpene emissions were well correlated with light, air temperature and relative humidity. Rates of emissions were also correlated with stomatal conductance and the rates of transpiration and photosynthesis. Almost all the individual terpenes identified followed the same pattern as total terpenes. The most abundant terpene was α-pinene, followed by sabinene + β-pinene, limonene, myrcene, camphene and α- phellandrene. Atmospheric terpene concentrations were also about 10 times higher in summer than in winter. A significant diurnal pattern with maxima at midday was observed, especially in summer. The increase by one order of magnitude in the concentrations of these volatile isoprenoids highlights the importance of local biogenic summer emissions in these Mediterranean forested areas which also receive polluted air masses from nearby or distant anthropic sources. Atmospheric concentrations of O3 and NO2 were also significantly higher in summer and at midday hours. In both seasons, concentrations of O3 were significantly correlated with concentrations of terpenes and NO2 in the air and with rates of terpene emission.
Keywords: montseny; Quercus ilex; Seasonality; Terpene air concentrations; Terpene emission rates; VOC

Seasonal changes in the daily emission rates of terpenes by Quercus ilex and the atmospheric concentrations of terpenes in the natural park of Montseny, NE Spain - Llusia, Joan; Penuelas, Josep; Seco, Roger; Filella, Iolanda (Journal of Atmospheric Chemistry, 2012)
We studied the daily patterns in the rates of terpene emissions by the montane holm oak, Quercus ilex, in three typical days of winter and three typical days of summer in Montseny, a natural park near Barcelona, and related them to the air concentrations of terpenes, ozone and NO2 . Terpene emission rates were about 10 times higher in summer than in winter. Emissions virtually stopped in the dark. In both seasons, rates of terpene emissions were well correlated with light, air temperature and relative humidity. Rates of emissions were also correlated with stomatal conductance and the rates of transpiration and photosynthesis. Almost all the individual terpenes identified followed the same pattern as total terpenes. The most abundant terpene was α-pinene, followed by sabinene + β-pinene, limonene, myrcene, camphene and α- phellandrene. Atmospheric terpene concentrations were also about 10 times higher in summer than in winter. A significant diurnal pattern with maxima at midday was observed, especially in summer. The increase by one order of magnitude in the concentrations of these volatile isoprenoids highlights the importance of local biogenic summer emissions in these Mediterranean forested areas which also receive polluted air masses from nearby or distant anthropic sources. Atmospheric concentrations of O3 and NO2 were also significantly higher in summer and at midday hours. In both seasons, concentrations of O3 were significantly correlated with concentrations of terpenes and NO2 in the air and with rates of terpene emission.
Keywords: montseny; Quercus ilex; Seasonality; Terpene air concentrations; Terpene emission rates; VOC

Chlorophyll fluorescence responses to temperature and water availability in two co-dominant Mediterranean shrub and tree species in a long-term field experiment simulating climate change - Ogaya, Romà; Penuelas, Josep; Asensio, Dolores; Llusia, Joan (Environmental and Experimental Botany, 2011)
A rain exclusion experiment simulating drought conditions expected in Mediterranean areas for the following decades (15% decrease in soil moisture) is being conducted since 1999 in a Mediterranean holm oak forest to study its response to the forecasted climatic changes for the coming decades. The maximum PSII quantum yield of primary photochemistry (Fv/Fm) was measured in Quercus ilex, and Phillyrea latifolia, the co-dominant species of the studied forest, from 1999 to 2009 in four plots: two of them were control plots and the other two plots received the rain exclusion treatment. In both species, the Fv/Fm values were highly dependent on air temperatures, and in a second term, in water availability. P. latifolia was the species with the larger decrease in Fv/Fm values induced by low air temperatures, while in hot seasons, the Fv/Fm values in P. latifolia were even higher than in Q. ilex. Rainfall exclusion decrease Fv/Fm values signiﬁcantly only in few monitoring dates. The most drought resistant species P. latifolia was more affected by the experimental rainfall exclusion than Q. ilex that instead lost number of leaves per tree. There was a synergic effect of drought stress and winter cold in P. latifolia not observed in Q. ilex, but a more conservative strategy in P. latifolia maintaining leaves with a down-regulation of the linear photosynthetic electron transport. These results indicate that, although other physiological and reproductive strategies at whole plant level must be also taken into account, the warmer and drier environment expected for the following decades could favour the species more sensitive to cold and more resistant to drought, the shrub P. latifolia, in detriment of the tree Q. ilex as already observed in the ﬁeld after severe heat-drought episodes.
Keywords: Chlorophyll ﬂuorescence; climate change; Cold; Drought; evergreen leaves; Fv/Fm; Heat; mediterranean forest; phillyrea latifolia; Quercus ilex

Indirect effects of tending ants on holm oak volatiles and acorn quality - Paris, Carolina I; Llusia, Joan; Penuelas, Josep (Plant signaling & behavior, 2011)
The indirect effect of ants on plants through their mutualism with honeydew-producing insects has been extensively investigated. Honeydew-producing insects that are tended by ants impose a cost on plant fitness and health by reducing seed production and/or plant growth. This cost is associated with sap intake and virus transmissions but may be overcompesated by tending ants if they deter or prey on hebivorous insects. The balance between cost and benefits depends on the tending ant species. In this study we report other indirect effects on plants of the mutualism between aphids and ants. We have found that two Lasius ant species, one native and the other invasive, may change the composition of volatile organic compounds (VOCs) of the holm oak (Quercus ilex) blend when they tend the aphid Lachnus roboris. The aphid regulation of its feeding and honeydew production according to the ant demands was proposed as a plausible mechanism that triggers changes in VOCs. Additionally, we now report here that aphid feeding, which is located most of the time on acorns cap or petiole, significantly increased the relative content of linolenic acid in acorns from holm oak colonized by the invasive ant. This acid is involved in the response of plants to insect herbivory as a precursor or jasmonic acid. No effect was found on acorn production, germination or seedlings quality. These results suggest that tending-ants may trigger the physiological response of holm oaks involved in plant resistance toward aphid herbivory and this response is ant species dependant
Keywords: invasive ants; jasmonic acid; linolenic acid; monoterpene emissions; tended aphid

Instantaneous and historical temperature effects on α -pinene emissions in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Llusia, Joan; Niinemets, Ülo; Noe, Steffen M.; Penuelas, Josep (Journal of Environmental Biology, 2011)
We compared the role of instantaneous temperature and temperature history in the determination of α-pinene emissions in Mediterranean conifer Pinus halepensis that stores monoterpenes in resin ducts, and in Mediterranean broad-leaved evergreen Quercus ilex that lacks such specialized storage structures. In both species, α-pinene emission rates (E) exhibited a significant exponential correlation with leaf temperature and the rates of photosynthetic electron transport (JCO 2 +O 2 ) started to decrease after an optimum at approximately 35 o C. However, there was a higher dependence of E on mean temperature of previous days than on mean temperature of current day for P. halepensis but not for Q. ilex. JCO 2 +O 2 showed a maximum relationship to mean temperature of previous 3 and 5 days for P. halepensis and Q. ilex respectively. We conclude that although the best correlation of emission rates were found for instantaneous foliar temperatures, the effect of accumulated previous temperature conditions should also be considered in models of monoterpene emission, especially for terpene storing species.
Keywords: acclimation; emission model; Pinus halepensis; previous climate effects; Quercus ilex

Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress

Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Sensitivity of terpene emissions to drought and fertilization in terpene-storing Pinus halepensis and non-storing Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Llusia, Joan (Physiologia Plantarum, 2007)
We studied the effects of water stress, fertilization and time course on foliar volatile terpene emission rates by Quercus ilex and Pinus halepensis in a garden experiment. The terpenes mostly emitted by both species were α-pinene, β-pinene, β-myrcene and Δ3-carene. P. halepensis emission rates (average 31.45 μg g−1 DM h−1) were similar to those of Q. ilex (average 31.71 μg g−1 DM h−1). The effects of drought (reduction to one-third of full watering) and fertilization (250 kg N ha−1, 250 kg P ha−1, or both) were different depending on the species: the drought treatment significantly increased the terpene emissions from Q. ilex by 33%, and the fertilization treatments reduced the terpene emissions from P. halepensis by 38%. Terpene emission rates increased with time course in parallel to raising summer temperatures in P. halepensis and Q. ilex, whose emission rates were temperature related (r = 0.42 and r = 0.68, respectively) and light related (r = 0.32 and r = 0.57, respectively). There was a positive relationship for P. halepensis, and a negative relationship for Q. ilex, between emission rates and relative water contents. No relationship was found between emission rates and N or P foliar concentrations. The results of this study show complex species-specific responses with stronger and faster short-term responses in terpene-non-storing than in storing species and indicate that terpene emissions may significantly change in the warmer, drier and more fertilized conditions predicted for the next decades in the Mediterranean region.
Keywords: Drought; Emission rates; Fertlization; mediterranean ecosystems (voyant); Pinus halepensis; Quercus ilex; storing and non-storing species; terpene

Sensitivity of terpene emissions to drought and fertilization in terpene-storing Pinus halepensis and non-storing Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Llusia, Joan (Physiologia Plantarum, 2007)
We studied the effects of water stress, fertilization and time course on foliar volatile terpene emission rates by Quercus ilex and Pinus halepensis in a garden experiment. The terpenes mostly emitted by both species were α-pinene, β-pinene, β-myrcene and Δ3-carene. P. halepensis emission rates (average 31.45 μg g−1 DM h−1) were similar to those of Q. ilex (average 31.71 μg g−1 DM h−1). The effects of drought (reduction to one-third of full watering) and fertilization (250 kg N ha−1, 250 kg P ha−1, or both) were different depending on the species: the drought treatment significantly increased the terpene emissions from Q. ilex by 33%, and the fertilization treatments reduced the terpene emissions from P. halepensis by 38%. Terpene emission rates increased with time course in parallel to raising summer temperatures in P. halepensis and Q. ilex, whose emission rates were temperature related (r = 0.42 and r = 0.68, respectively) and light related (r = 0.32 and r = 0.57, respectively). There was a positive relationship for P. halepensis, and a negative relationship for Q. ilex, between emission rates and relative water contents. No relationship was found between emission rates and N or P foliar concentrations. The results of this study show complex species-specific responses with stronger and faster short-term responses in terpene-non-storing than in storing species and indicate that terpene emissions may significantly change in the warmer, drier and more fertilized conditions predicted for the next decades in the Mediterranean region.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought; Emission rates; Fertlization; mediterranean ecosystems (voyant); Pinus halepensis; Quercus ilex; storing and non-storing species; terpene

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Sustained accumulation of methyl salicylate alters antioxidant protection and reduces tolerance of holm oak to heat stress - Llusia, Joan; Penuelas, Josep; Munné-Bosch, Sergi (Physiologia Plantarum, 2005)
Methyl salicylate (MeSA) is thought to have a major role in biotic and abiotic stresses by acting as a signal to trigger the oxidative burst, which is needed to activate gene expression in plant stress responses. To assess the potential effects of sustained foliar accumulation of MeSA on plant stress tolerance, the extent of photo- and antioxidant protection, lipid peroxidation and visual leaf area damage were evaluated in MeSA-treated (c. 60 nl l−1 in air) and control holm oak (Quercus ilex L.) plants exposed to heat stress. Control plants showed an increase in foliar MeSA levels up to 1.8 nmol [gDW]−1 as temperature increased and they displayed tolerance to temperatures as high as 45°C, which might be attributed, at least in part, to enhanced xanthophyll de-epoxidation and increases in ascorbate and α-tocopherol. MeSA-treated plants showed a sustained foliar accumulation of this compound, with values ranging from 10 to 23 nmol [gDW]−1 throughout the experiment. These plants showed lower ascorbate and tocopherol levels and higher oxidative damage at 50°C than controls, as indicated by enhanced malondialdehyde levels and leaf area damage and lower maximum efficiency of PSII photochemistry (Fv/Fm ratio). These results demonstrate that a sustained foliar accumulation of MeSA is detrimental to plant function and that it can reduce thermotolerance in holm oak by altering antioxidant defences.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: antioxidant protection (voyant); foliar MeSA accumulation; heat stress; Holm oak; methyl salicylate

Linking photorespiration, monoterpenes and thermotolerance in Quercus - Penuelas, Josep; Llusia, Joan (New Phytologist, 2002)
* • The functions of two important plant processes, photorespiration and monoterpene production remain controversial. Here, we investigated one possible function, that of protection of plants from photodamage at high temperatures. * • Fluorescence, reflectance, monoterpene concentrations and visual leaf damage were measured in Quercus ilex seedlings exposed to temperature increases from 25 to 50°C (in 5°C steps) under photorespiratory (21% O 2 ) or nonphotorespiratory (2% O 2 ) atmospheres, and under control or terpene fumigation conditions. * • Lower variable to maximum fluorescence ratio (Fv : Fm: potential photochemical efficiency of photosystem II, PSII) and electron transport rate (ETR) were found in nonphotorespiratory conditions at temperatures greater than 35°C. Monoterpene concentrations were also lower, and leaf damage greater, in the low O 2 atmospheres. Monoterpene fumigation, which increased the foliar terpene concentrations by two- to four-fold, increased the photochemical efficiency between 35°C and 50°C, and decreased leaf damage, only under the nonphotorespiratory conditions. * • These results provide evidence that: photorespiration decreases photodamage, especially at high temperatures; photorespiration increases monoterpene production; plants are able to acquire exogenous monoterpenes and the acquisition response to temperature follows the stomatal conductance response; and monoterpenes can replace photorespiration in protection from photodamage at high temperatures, possibly by scavenging oxygen-reactive species, but they do not provide additional thermotolerance.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: electron transport rate (ETR); fumigation; Fv : Fm; limonene; Monoterpenes; photochemical reflectance index (PRI); photorespiration; thermotolerance; α-pinene

Linking photorespiration, monoterpenes and thermotolerance in Quercus - Penuelas, Josep; Llusia, Joan (New Phytologist, 2002)
* • The functions of two important plant processes, photorespiration and monoterpene production remain controversial. Here, we investigated one possible function, that of protection of plants from photodamage at high temperatures. * • Fluorescence, reflectance, monoterpene concentrations and visual leaf damage were measured in Quercus ilex seedlings exposed to temperature increases from 25 to 50°C (in 5°C steps) under photorespiratory (21% O 2 ) or nonphotorespiratory (2% O 2 ) atmospheres, and under control or terpene fumigation conditions. * • Lower variable to maximum fluorescence ratio (Fv : Fm: potential photochemical efficiency of photosystem II, PSII) and electron transport rate (ETR) were found in nonphotorespiratory conditions at temperatures greater than 35°C. Monoterpene concentrations were also lower, and leaf damage greater, in the low O 2 atmospheres. Monoterpene fumigation, which increased the foliar terpene concentrations by two- to four-fold, increased the photochemical efficiency between 35°C and 50°C, and decreased leaf damage, only under the nonphotorespiratory conditions. * • These results provide evidence that: photorespiration decreases photodamage, especially at high temperatures; photorespiration increases monoterpene production; plants are able to acquire exogenous monoterpenes and the acquisition response to temperature follows the stomatal conductance response; and monoterpenes can replace photorespiration in protection from photodamage at high temperatures, possibly by scavenging oxygen-reactive species, but they do not provide additional thermotolerance.
Keywords: electron transport rate (ETR); fumigation; Fv : Fm; limonene; Monoterpenes; photochemical reflectance index (PRI); photorespiration; thermotolerance; α-pinene

Seasonal emission of monoterpenes by the Mediterranean tree Quercus ilex in field conditions: Relations with photosynthetic rates, temperature and volatility - Penuelas, Josep; Llusia, Joan (Physiologia Plantarum, 1999)
The relationships of monoterpene emission with temperature, light, photosynthesis and stomatal conductance (gs) were studied in Quercus ilex L. trees throughout the four annual seasons under field conditions. The highest monoterpene emission was measured in spring and summer (midday average of 11 μg [g DW]−1 h−1), whereas the lowest rates were found in autumn and winter (midday averages of 0.51 and 0.23 μg [g DW]−1 h−1, respectively). In spring and summer, limonene was the monoterpene emitted at highest rate (midday averages of 5.27–6.69 μg [g DW]−1 h−1), whereas α-pinene was emitted the most in autumn and winter (midday averages of 0.31 μg [g DW]−1 h−1). The monoterpenes limonene, α-pinene and β-pinene represented about 75–95% of total detected monoterpenes. The total monoterpene emission rates represented about 0.04% of carbon fixed in autumn, 0.17% in winter, 0.84–2.51% in spring and 1.22–5.13% in summer. Significant correlations of total monoterpene emission with temperature were found when considering either summer emission or the emission over the entire year, whereas significant correlations with net photosynthetic rates were only found when considering summer season. Among individual terpenes, the most volatile, α-pinene and β-pinene, were more correlated with temperature than with net photosynthetic rates whereas the less volatile limonene was more correlated with net photosynthetic rate. Thus, under field conditions it seems that dependency of monoterpene emission on photosynthetic rate or temperature is partly related with volatility of the compounds. Influences of seasonality, temperature, photosynthetic rates and volatility should be considered in inventories and models of emission rates in Mediterranean ecosystems.
Keywords: monoterpene emission rates; photosynthetic rates; seasonal variation (voyant); Temperature; volatility